Пошук статевоспецифічних ДНК-маркерів у лососевих видів риб - Рудь, Ю.П.; Залоїло, О.В.; Бучацький, Л.П. (Фактори експериментальної еволюції організмів, 2016)
Aim. To analyze the nucleotide sequences of sex-specific DNA-markers of salmonid fishes and to develop the polymerase
chain reaction for rapid diagnostic of sex in rainbow trout Oncorhynchus mykiss, brook trout Salmo trutta, huchen Hucho
hucho and grayling Thymallus thymallus. Methods. The methods of DNA extraction, oligonucleotide primer selection
involving NCBI, BLAST, MEGA 6.0 and Vector NTI 11 software, conventional PCR assay, Sanger sequencing, ClustalW
algorithm for sequence analyzing were used. Results. The PCR-products were in size of 880, 607, 521 and 558 for
rainbow trout, brook trout, grayling and huchen respectively. The specify of amplification was determined by nucleotide
sequence analysis of PCR-products. All amplified fragments were referred to sex-specific locuses of Y chromosomes in
males of investigated fish species. Conclusions. The sex determination in above mentioned fish species and identification
of genotypic males under process of hormonal sex reversion can be provided using conventional PCR. Present method
relates to rapid diagnostics because the data analysis and return of results back to fish farm take one single day.
Keywords: DNA-markers, PCR diagnostics, sex reversion, salmon raising.